Fotogrammetria Subacquea e Rilievo 3D di Precisione di Strutture Galleggianti o Semi-Sommerse - Menna, Fabio; Nocerino, Erica; Troisi, Salvatore; Remondino, Fabio (GEOmedia, 2014)
The article presents an innovative methodo logy for the 3D surveying and mod eling of floating and semi-submerged objects. Photogramm etry is used for surveying both the underwater and emerged parts of the object and the two surveys are com bined together by means of special rigid orientation devices. As examp le, a challenging project is repo rted, i.e. a large shipwreck (almo st 300 meters long) interested by a 52 m long leak at the waterline. The article co vers the entire workflow, starting from the preparation and data acquisition do wn to the realization of the digital 3D mod el by means of dense image matching proc edures as well as deformation analyses and comp arison with the craft original plane.